2014
DOI: 10.1080/02673843.2014.881295
|View full text |Cite
|
Sign up to set email alerts
|

Ethnic-related diversity engagement differences in intercultural sensitivity among Malaysian undergraduate students

Abstract: This survey examines the association of ethnic-related diversity engagement with three interrelated dimensions of intercultural sensitivity among students in ap ublic university with am ulti-ethnic, multi-religious student population. At otal of 447 respondents provided the data for analysis. Using multivariate analysis of variance (MANOVA), the findings suggest that the level of intercultural sensitivity among students is positively associated with students' level of ethnic-related diversity engagement, and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(11 citation statements)
references
References 26 publications
0
11
0
Order By: Relevance
“…For this research, we decided to use the definition of intercultural sensitivity proposed by Chen and Starosta [22]. The authors emphasized the differences between the idea of intercultural adequacy and potency, and this counters confusion in understanding the concept of intercultural sensitivity and gives a more comprehensive theoretical model to gauge this ideology [23,24].…”
Section: Introductionmentioning
confidence: 99%
“…For this research, we decided to use the definition of intercultural sensitivity proposed by Chen and Starosta [22]. The authors emphasized the differences between the idea of intercultural adequacy and potency, and this counters confusion in understanding the concept of intercultural sensitivity and gives a more comprehensive theoretical model to gauge this ideology [23,24].…”
Section: Introductionmentioning
confidence: 99%
“…As reviewed, intercultural communication sensitivity is closely related to various linguistic, psychological, educational and demographic variables such as proficiency in and contact with the target language and culture, willingness to communicate in a SL/FL, gender, and language learning motivation. Nevertheless, some studies have revealed different findings (Bae & Song, 2017;Çiloğlan & Bardakçı, 2019;Liu, 2018b;Morales, 2017;Tamam & Krauss, 2014;Yilmaz, 2019;Yurtseven & Altun, 2015). Yurtseven and Altun's (2015) analyses of 220 questionnaires collected from pre-service teachers in America indicated that there was no significant difference in the ICS levels in regard to gender, study abroad experience, and contact with the target language and culture.…”
Section: Introductionmentioning
confidence: 99%
“…Since all of the study data obtained were based on the students' responses, it should be taken into account that the students might have given biased information, which can be considered as another limitation of the study. There are very few studies about this scale and intercultural effectiveness in different sampling such as medical students (Nameni and Dowlatabadi, 2019), students of in a public university (Tamam and Krauss, 2017), university students from USA and Germany (Fritz et al, 2005). The small sample size is a limitation of the work, and that the results can only be taken as a first approximation.…”
Section: Limitationsmentioning
confidence: 99%